First host plant records for Iridopsis hausmanni Vargas (Lepidoptera, Geometridae) in the coastal valleys of northern Chile - Vargas,Héctor A. (2014)
First host plant records for Iridopsis hausmanni Vargas (Lepidoptera, Geometridae) in the coastal valleys of northern Chile. The trees Haplorhus peruviana Engl. and Schinus molle L. (Anacardiaceae) are mentioned as the first host plant records for the little known native moth Iridopsis hausmanni Vargas, 2007 (Lepidoptera, Geometridae, Ennominae) in the coastal valleys of the northern Chilean Atacama Desert. This is also the first record of Anacardiaceae as host plant for a Neotropical species of Iridopsis Warren, 1894.